Acute crack cocaine exposure induces genetic damage in multiple organs of rats - Moretti, Eduardo Gregolin; Yujra, Veronica Quispe; Claudio, Samuel Rangel; Silva, Marcelo Jose Dias [UNESP]; Vilegas, Wagner [UNESP]; Pereira, Camilo Dias Seabra; de Oliveira, Flavia; Ribeiro, Daniel Araki (Springer Nature, 2016)
Crack cocaine is a very toxic product derived from cocaine. The aim of this study was to evaluate genetic damage in multiple organs of rats following acute exposure to crack cocaine. A total of 20 Wistar rats were distributed into four groups (n = 5), as follows: 0, 4.5, 9, and 18 mg/kg body weight (b.w.) of crack cocaine administered by intraperitoneal route (i.p.). All animals were killed 24 h after intraperitoneal (i.p.) injection. The results showed that crack cocaine increased the number of micronucleated cells in bone marrow cells exposed to 18 mg/kg crack cocaine (p < 0.05). Peripheral blood and liver cells presented genetic damage as depicted by single cell gel (comet) assay at 9 and 18 mg/kg doses (p < 0.05). Immunohistochemistry data revealed significant increase in 8-hydroxy-20-deoxyguanosine (8-OHdG) immunoexpression in hepatocytes of animals exposed to crack cocaine at 9 and 18 mg/kg (p < 0.05) when compared with negative controls. Taken together, our results demonstrate that crack cocaine is able to induce genomic damage in multiple organs of Wistar rats.
Keywords: Crack cocaine; DNA damage; Genomic instability; Rat